Multiple orifices are better than single in the endoscopic treatment of pancreatic pseudocysts - Tomasz Miłek; Piotr Ciostek; Maciej Kielar; Mirosław Jarosz; Kuba Słowik; Robert Petryka; Tomasz Błalejczyk (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The aim of this study was to compare the surgical drainage of large, symptomatic pancreatic cysts (>5 cm) with single- and multi-channel endoscopic drainage. Materials and Methods: In the period 2005-2010, we treated 112 patients with post-inflammatory pancreatic cysts. Thirty-six patients underwent surgical internal drainage. The remaining group of patients was treated endoscopically. In 28 of them, drainage was performed by anastomosing the cyst to the gastrointestinal tract using a single pig tail drain and then widening the channel to a diameter of 15 mm. Forty-eight patients underwent multi-channel cystic drainage. It consisted of connecting the cyst to the stomach and/or duodenum using at least 3 drains. Each connection was widened to a minimum diameter of 15 mm to ensure free drainage of the morphotic elements of the cyst. Each procedure was preceded by abdominal computed tomography to determine the exact location of the cyst in relation to the gastrointestinal tract and a Doppler ultrasound scan to determine the location of the blood vessels modeling on its surface. Results: In 48 patients with multi-channel drainage, there was no obstruction of the anastomosis, and cysts closed within 4 months. The drains were removed after about 3 months. The created channels were patent for about 3-4 weeks, which was enough to completely close the cyst. Conclusion: Multi-channel endoscopic anastomosis of pancreatic cyst to the gastrointestinal tract is a very effective method for drainage of large post-inflammatory pancreatic cysts, comparable in terms of effectiveness with the surgical method but less invasive. Turkish Başlık: Pankreatik psödokistlerin endoskopik tedavisinde çoklu orifisler tekten daha iyidir Anahtar kelimeler: Pankreas kisti, çok-kanallı endoskopik anastomoz, Doppler ultrason Arkaplan/Amaç: Bu çalışmanın amacı, büyük, semptomatik pankreas kistlerinin (>5 cm) tek ve çok kanallı endoskopik drenajı ile cerrahi drenajını karşılaştırmaktı. Yöntemler ve Gereçler: 2005-2010 döneminde, biz post-inflamatuar pankreas kistleri olan 112 hastayı tedavi ettik. Otuz altı hastaya cerrahi internal drenaj uygulandı. Hastaların geri kalan grubu endoskopik olarak tedavi edildi. Bunların 28’inde, tek bir domuz kuyruğu dren kullanılarak ve daha sonra kanal 15 mm’lik bir çapa genişletilerek gastrointestinal kanala kistin anastomoz edilmesi ile drenaj gerçekleştirildi. Kırk sekiz hastada çok kanallı kistik drenaj uygulandı. Bu, kistin en az 3 dren kullanılarak mide ve/veya duodenuma birleştirilmesini içermekteydi. Her bağlantı kistin morfotik elemanlarının serbest drenajını sağlamak için minimum 15 mm çapa genişletildi. Her prosedür öncesi gastrointestinal kanalla ilişkili kistin tam lokalizasyonunu saptamak için abdominal bilgisayarlı tomografi ve yüzeyindeki kan damarları modellemesinin konumunu belirlemek için Doppler ultrason taraması yapıldı. Bulgular: Çok-kanallı drenaj ile 48 hastada, hiçbir anastomoz tıkanması olmadı ve kistler 4 ay içinde kapandı. Drenler yaklaşık 3 ay sonra çıkarıldı. Oluşturulan kanallar kistin tamamen kapanması için yeterli olan yaklaşık 3-4 hafta süre için açıktı. Sonuç: Gastrointestinal kanala pankreas kistinin çok-kanallı endoskopik anastomozu büyük post-inflamatuar pankreas kistlerinin drenajı için çok etkili bir metottur ve cerrahi metot ile etkinliği açısından kıyaslanabilir olup daha az invazivdir.